A series of Ln4III clusters: Dy4 single molecule magnet and Tb4 multi-responsive luminescent sensor for Fe3+, CrO42−/Cr2O72− and 4-nitroaniline. Issue 23 (3rd April 2018) - Qin, Yaru; Ge, Yu; Zhang, Shasha; Sun, Hao; Jing, Yu; Li, Yahong; Liu, Wei
Abstract : Five tetranuclear lanthanide clusters were synthesized. Dy4 complex exhibits single molecule magnet (SMM) behavior and Tb4 compound shows sensing properties towards Fe 3+, CrO4 2−, Cr2 O7 2− and 4-nitroaniline (4-NA). Abstract : Five tetranuclear lanthanide clusters of compositions [Ln4 L4 (NO3 )2 (Piv)2 ]·2CH3 OH (Ln = Gd (1 ), Tb (2 ), Dy (3 ), Ho (4 ), Er (5 ); H2 L = 2-(((2-hydroxy-3-methoxybenzyl)imino)methyl)-6-methoxyphenol; Piv = pivalic acid) were synthesized under solvothermal conditions. The structures of1–5 were characterized by single-crystal X-ray crystallography. Complexes1–5 possess a zig-zag topology with [Ln4 O6 ] cores being formed by the fusion of oxygen atom-bridged two [Ln2 O2 ] moieties. Direct-current magnetic susceptibility studied in the 2–300 K range revealed weak antiferromagnetic interactions in1, 2, 4, 5 and ferromagnetic interactions in3 . Complex3 exhibits single molecule magnet (SMM) behavior. The luminescence studies indicated that complex2 can serve as highly sensitive and selective luminescent materials for Fe 3+, CrO4 2−, Cr2 O7 2− and 4-nitroaniline (4-NA), demonstrating that complex2 should be a potential candidate for multi-responsive luminescent sensor.